Influences of Xeno-Free Media on Mesenchymal Stem Cell Expansion for Clinical Application - Bui, Hue Thi Hong (Tissue Eng Regen Med, 2020)
Mesenchymal stem/stromal cells (MSCs) are multipotent somatic stem/progenitor cells that can be isolated from various tissues and have attracted increasing attention from the scientific community. This is due to MSCs showing great potential for incurable disease treatment, and most applications of MSCs involve tissue degeneration and treatment of immune- and inflammation-mediated diseases. Conventional MSC cultures contain fetal bovine serum (FBS), which is a common supplement for cell development but is also a risk factor for exposure to animal-derived pathogens. To avoid the risks resulting from the xenogeneic origin and animal-derived pathogens of FBS, xeno-free media have been developed and commercialized to satisfy MSC expansion demands for human clinical applications. This review summarized and provided an overview of xeno-free media that are currently used for MSC expansion. Additionally, we discussed the influences of different xeno-free media on MSC biology with particular regard to cell morphology, surface marker expression, proliferation, differentiation and immunomodulation. The xeno-free media can be serum-free and xeno-free media or media supplemented with some human-originating substances, such as human serum, human platelet lysates, human umbilical cord serum/plasma, or human plasma-derived supplements for cell culture medium. These media have capacity to maintain a spindle-shaped morphology, the expression of typical surface markers, and the capacity of multipotent differentiation and immunomodulation of MSCs. Xeno-free media showed potential for safe use for human clinical treatment. However, the influences of these xeno-free media on MSCs are various and any xeno-free medium should be examined prior to being used for MSC cultures.